Rate, timing and causes of neonatal deaths in rural India: implications for neonatal health programmes. - Baqui AH; Darmstadt GL; Williams EK; Kumar V; kiran TU; Panwar d; Srivastava VK; Ahuja R; Black RE; Santosham M (Bulletin of the World Health Organization, 2006)
OBJECTIVETo assess the rates, timing and causes of neonatal deaths and the burden of stillbirths in rural Uttar Pradesh, India. We discuss the implications of our findings for neonatal interventions.METHODSWe used verbal autopsy interviews to investigate 1048 neonatal deaths and stillbirths.FINDINGSThere were 430 stillbirths reported, comprising 41% of all deaths in the sample. Of the 618 live births, 32% deaths were on the day of birth, 50% occurred during the first 3 days of life and 71% were during the first week. The primary causes of death on the first day of life (i.e. day 0) were birth asphyxia or injury (31%) and preterm birth (26%). During days 1-6, the most frequent causes of death were preterm birth (30%) and sepsis or pneumonia (25%). Half of all deaths caused by sepsis or pneumonia occurred during the first week of life. The proportion of deaths attributed to sepsis or pneumonia increased to 45% and 36% during days 7-13 and 14-27, respectively.CONCLUSIONStillbirths and deaths on the day of birth represent a large proportion of perinatal and neonatal deaths, highlighting an urgent need to improve coverage with skilled birth attendants and to ensure access to emergency obstetric care. Health interventions to improve essential neonatal care and care-seeking behavior are also needed, particularly for preterm neonates in the early postnatal period. Copyright © 2006 World Health Organization